Theory and practice of modern antenna range measurements Volume 1 Clive Parini, Stuart Gregson, John McCormick, Daniël Janse van Rensburg and Thomas Eibert - Parini, Clive; Gregson, Stuart Fraser; McCormick, John (Lead radar systems engineer); Van Rensburg, Daniël Janse; Eibert, Thomas (SciTech Publishing, an imprint of The Institution of Engineering and Technology, 2020)
This greatly expanded, co-authored, two-volume text provides a comprehensive introduction and explanation of both the theory and practice of modern antenna measurements, from their most basic postulates and assumptions, to the intricate details of their applications in various demanding modern measurement scenarios. Starting with an initial examination of the properties of antennas that allow them to enhance the free-space interaction of electronic systems, the authors then introduce direct far-field and indirect far-field forms of antenna measurements and their various implementations. Detailed descriptions are given of the direct far-field measurement technique CATR (Compact Antenna Test Ranges), Body-Centric measurements, and detailed developments of standard planar, cylindrical, spherical and non-canonical near-field techniques; and includes a through treatment of near-field range error budgets which are an indispensable part of antenna metrology. The books conclude with recent advances in measurement techniques such as aperture diagnostics, phase-less antenna metrology, error correction, and range multi-path suppression techniques. Extensive examples illustrate the concepts and techniques covered. This second edition is thoroughly expanded and now includes new chapters on near-field to far-field transforms from non-canonical surfaces, electromagnetic modelling of CATRs and near-field antenna measurement systems. In addition there is an expanded chapter on coordinate systems, polarization bases and antenna pattern plotting and new sections on more specialized topics such as 5G and Radome measurements.
Keywords: Antennas (Electronics); elektronické knihy; electronic books